Eosinophilic folliculitis. - Diociaiuti, A.; Paone, C.; Boldrini, R.; Giraldi, L.; El Hachem, M. (European Journal of Pediatric Dermatology, 2007)
Eosinophilic pustular folliculitis (EPF) is a chronic rare disease characterized by the presence of follicular papules and pustules. A 40-month-old child presented papular and pomphoid lesions on the trunk, extremities and scalp. Peripheral blood tests showed eosinophilia and skin biopsy confirmed the diagnosis of EPF. Treatment with prednisone led to complete remission.